Rural tourism entrepreneurship success factors for sustainable tourism village: Evidence from Indonesia - Dwiesty Dyah Utami; Wawan Dhewanto; Yuliani Dwi Lestari (Cogent Business & Management, 2023)
This study aims to examine the success factors and build the framework of rural tourism entrepreneurship for a sustainable tourism village. This is an important research topic, as 44.28% population in the world live in rural areas; specifically 44.02% population in Indonesia resides in a rural area which indicates how important rural areas are for future development. This study used a purposive sampling technique to determine the priority issues of the sustainability of the tourism village. The data was gathered from semi-structured interviews with actors' influential in the success of tourism villages. This study was conducted with a qualitative approach and a case study design. This study uses content analysis in describing the findings from the collected data to better understand the case study. It focuses on a case of six tourism villages in Indonesia that have received awards as sustainable tourism villages, as it might be adopted by the other tourism villages. The results revealed ten factors for creating successful sustainable tourism village through rural tourism entrepreneurship. Those factors are income management, business unit development, economic growth, mutual cooperation, collaboration, innovation, creativity, environmental awareness, resource management, and visitor management. These 10 factors are further grouped into three dimensions (economic, social, and environmental sustainability). The study makes new framework of rural tourism entrepreneurship and useful for the strategy and decision-making process.
Keywords: 650; rural tourism entrepreneurship; rural tourism management; success factor; sustainable tourism; tourism entrepreneurship; tourism management; tourism resources